Hox gene regulation in the central nervous system of Drosophila - Gummalla, Maheshwar; Galetti, Sandrine; Maeda, Robert K.; Karch, François (Frontiers in Cellular Neuroscience, 2014)
Hox genes specify the structures that form along the anteroposterior (AP) axis of bilateria. Within the genome, they often form clusters where, remarkably enough, their position within the clusters reflects the relative positions of the structures they specify along the AP axis. This correspondence between genomic organization and gene expression pattern has been conserved through evolution and provides a unique opportunity to study how chromosomal context affects gene regulation. In Drosophila, a general rule, often called “posterior dominance,” states that Hox genes specifying more posterior structures repress the expression of more anterior Hox genes. This rule explains the apparent spatial complementarity of Hox gene expression patterns in Drosophila. Here we review a noticeable exception to this rule where the more-posteriorly expressed Abd-B Hox gene fails to repress the more-anterior abd-A gene in cells of the central nervous system (CNS). While Abd-B is required to repress ectopic expression of abd-A in the posterior epidermis, abd-A repression in the posterior CNS is accomplished by a different mechanism that involves a large 92 kb long non-coding RNA (lncRNA) encoded by the intergenic region separating abd-A and Abd-B (the iab8ncRNA). Dissection of this lncRNA revealed that abd-A is repressed by the lncRNA using two redundant mechanisms. The first mechanism is mediated by a microRNA (mir-iab-8) encoded by intronic sequence within the large iab8-ncRNA. Meanwhile, the second mechanism seems to involve transcriptional interference by the long iab-8 ncRNA on the abd-A promoter. Recent work demonstrating CNS-specific regulation of genes by ncRNAs in Drosophila, seem to highlight a potential role for the iab-8-ncRNA in the evolution of the Drosophila Hox complexes.